Risk assessment of hazardous impacts on urbanization and industrialization activities based upon toxic substances - T. Salem; Sh.S. Ahmed; M. Hamed; G.H. Abd ElAziz (Global Journal of Environmental Science and Management)
A risk assessment study was conducted to predict the expected hazardous influence on the ecosystem resulted from urbanization and industrialization activities at Helwan area, Egypt. To achieve these goals, soils, plants and water samples were collected from Helwan area, and their total concentrations of inorganic contaminants (Cd, Cr, Co, Cu, Fe, Mn, Ni, Pb, and Zn) and organic pollutants; such as Phenol and hydrocarbons were measured. The obtained results showed that, the concentrations of organic contaminants in water streams and surrounding soils recorded high concentration values than the permissible limits, while inorganic elements were within the safe limits for irrigation. In addition, soils irrigated with the effluents of industrial units recorded high values of inorganic and organic contaminants. Consequently, the levels of these contaminants were high in plant tissues grown thereon; especially the edible parts. Risk assessment based on available Predicted No Effect Concentration values for the aquatic and terrestrial environment was performed. Inorganic elements were expected to cause serious hazard problems for both aquatic organisms and soil microorganisms. The impact of these pollutants on human health was calculated using daily metals intake of inorganic metals via consumption of edible plants. Hazard index values proved that concentrations of Cr may cause serious hazard problems for humans in this area; especially, children.